2010
DOI: 10.4028/www.scientific.net/ast.63.1
|View full text |Cite
|
Sign up to set email alerts
|

Spray Freeze Granulation of Nano Powders for Die Pressing

Abstract: The processing of nanocrystalline yttria doped zirconia powder via dry forming routes has been investigated via the granulation of the powder using spray freeze drying (SFD). Free-flowing and crushable powders suitable for either die or isosatic pressing have been achieved via the combination of SFD with additions of up to 2 vol% of Freon 11; the latter reducing the strength of the granules whilst not affecting the powder flowability into the die. The approach has allowed relic-free green bodies of up to 55% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Initially inspired by the demonstrations of the high novelty and wide‐ranging applicability of non‐thermal microwave effects (NTME) in materials processing at the first microwave processing symposium sponsored by the Materials Science & Technology (MS&T) Forum in 2009, this author also learned that the underlying science required to guide further development of this novel processing technology was then quite preliminary 9,10 . Since then, numerous rationale and theories of NTME in microwave processing were advanced and refined in the materials community, but with limited applications 11–19 . For instance, the conception on ponderomotive action of a microwave‐field (MF) may merely provide a rationale of materials transformation/transport enhancements in ionic crystalline solids 12–14 ; while the hypothesis of MF‐induced acoustic (hypersound) energy, which augments mass transports and chemical reactions, may only hold for NTME creation in piezoelectric materials 11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially inspired by the demonstrations of the high novelty and wide‐ranging applicability of non‐thermal microwave effects (NTME) in materials processing at the first microwave processing symposium sponsored by the Materials Science & Technology (MS&T) Forum in 2009, this author also learned that the underlying science required to guide further development of this novel processing technology was then quite preliminary 9,10 . Since then, numerous rationale and theories of NTME in microwave processing were advanced and refined in the materials community, but with limited applications 11–19 . For instance, the conception on ponderomotive action of a microwave‐field (MF) may merely provide a rationale of materials transformation/transport enhancements in ionic crystalline solids 12–14 ; while the hypothesis of MF‐induced acoustic (hypersound) energy, which augments mass transports and chemical reactions, may only hold for NTME creation in piezoelectric materials 11 .…”
Section: Introductionmentioning
confidence: 99%
“…The most recently proposed MF‐enhanced surface‐charge mobility theory was specifically formulated to comprehend the reactivity and diffusion enhancements of electrically conductive solids in microwave heating 17 . While these theories have promoted the understanding of the NTME in microwave materials processing, their validities remain limited to certain specific materials systems and processing conditions 11–19 …”
Section: Introductionmentioning
confidence: 99%
“…However, both the density and strength of the sintered materials obtained from the high‐density granules are characterized by sufficiently low values owing to a flaw formation. J. Binner et al 19 show that the addition of 1 vol.% Freon to the suspension promotes the better breakability of YSZ SFD granules containing 20‐vol.% solids. S. Ghanizadeh et al 15 showed that the addition of a 2% Freon 11 foaming agent contributed to the better breakability of Al 2 O 3 SFD granules obtained from a suspension with a solids loading of 59 wt.%.…”
Section: Introductionmentioning
confidence: 99%
“…According to T. Moritz and A. Nagy 18 , the strength of SFD granules is four times lower than SD granules. A sufficient number of studies determined the strength of single granules 12,18,19 . According to B. Raghupathy and J. Binner 12 , the strength of SFD granules directly depends on the solids content of the initial suspension.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 reports a subdivision of the papers on the basis of the grain size of the developed final products: For the elaboration of Figure 1, only the paper reporting an experimental procedure to produce nanozirconia-made components were considered. In Figure 2, the geographical provenience of all the 74 analyzed scientific papers [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,…”
Section: Introductionmentioning
confidence: 99%